2007
DOI: 10.1088/0957-4484/18/27/275705
|View full text |Cite
|
Sign up to set email alerts
|

SiO2-coated porous anodic alumina membranes for high flow rate electroosmotic pumping

Abstract: Electroosmotic pumping has been extensively used in lab-on-a-chip devices and micropumps for microelectronic cooling. High flow rate per unit area with a low applied voltage is a key performance requirement to achieve compact design and efficient operation. In this paper, we report work on using SiO2-coated porous anodic alumina membranes for high flow rate electroosmotic pumping under low applied voltages. High quality porous alumina membranes of controllable pore diameters in the range of 30–100 nm and pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
3
41
1
Order By: Relevance
“…In Table 1 we show that this figure of merit exceeds low-voltage EOPs fabricated from porous silicon (10), alumina (11), and track-etched polymer (14) by three orders of magnitude. Normalized flow rates for ultrathin pnc-Si EOPs are also 20 times higher than carbon nanotube (CNT) EOPs, which are considered to have unique properties due to a slippery surface (15).…”
Section: Significancementioning
confidence: 94%
See 2 more Smart Citations
“…In Table 1 we show that this figure of merit exceeds low-voltage EOPs fabricated from porous silicon (10), alumina (11), and track-etched polymer (14) by three orders of magnitude. Normalized flow rates for ultrathin pnc-Si EOPs are also 20 times higher than carbon nanotube (CNT) EOPs, which are considered to have unique properties due to a slippery surface (15).…”
Section: Significancementioning
confidence: 94%
“…Note that only a small portion of the applied voltage V app falls across the membrane. One method to determine the transmembrane voltage V TM is through the electrical resistance in the system (11,16),…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The packed beads increase the interfacial area available for EO flow, thereby increasing maximum pressure; pressures above 2 MPa have been reported (Zeng et al 2001). As an alternative to the use of packed beads, an innovative EO pump method using porous anodic alumina (PAA) was reported (Vajandar et al 2007). This pump had the highest normalized flow rate as compared to any previous EO pump at lower voltages.…”
Section: Electroosmoticmentioning
confidence: 99%
“…The authors also found that the flow rate decreased with decreasing porosity, as expected. The effect of surface charge on EOF was observed with a two-orders-of-magnitude increase in the maximum flow rate for SiO 2 -coated AAMs compared to uncoated AAMs using a borate buffer (Vajandar et al 2007). Another study looked at the effect of three different AAM pore diameters of 25, 46 and 240 nm) on ion transport and found that ion diffusion coefficients decreased with decreasing pore diameter for ions with the same charge as the pore wall (Romero et al 2012).…”
Section: Introductionmentioning
confidence: 97%